Penentuan Penerima Bantuan dengan Program Miskin Berprestasi Menggunakan Metode Combined Compromise Solution (CoCoSo) - Sallaby, Achmad Fikri; Kanedi, Indra; Sari, Venny Novita; Alinse, Rizka Tri; Supardi, Reno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Educational assistance programmes from the government and other parties allow people to focus on education without being burdened by costs. In Indonesia, various aid programmes are available, including Bidik Misi for new students and special programmes for active students in need. These programmes aim to help poor, high-achieving students continue their education. However, there are problems in the determination of aid recipients. Aid funds are often misused by some students for hedonistic lifestyles. This is due to a selection system that is not objective and is still influenced by